Demonstration of a widely tunable digital supermode distributed Bragg reflector laser as a versatile source for near-infrared spectroscopy - Ciaffoni, L; Hancock, G; Hurst, P; Kingston, M; Langley, C; Peverall, R; Ritchie, G; Whittaker, K (2013)
In this paper we report the characterization of a novel, widely tunable, diode laser source operating over the full telecom L-band (1563-1613 nm), namely the digital supermode distributed Bragg reflector (DS-DBR) laser, and its application to multi-wavelength gas sensing via absorption strategies. The spectroscopic performance of the laser has been assessed by investigating the ro-vibrational spectrum of CO2, and wavelength modulation spectroscopy was accomplished for proof-of-principle sensitive measurements in discrete spectral regions. © 2011 Springer-Verlag.